PERAN GURU OLAHRAGA DALAM MENINGKATKAN KEGIATAN EKSTRAKURIKULER SEPAK BOLA DI MI NEGERI 7 BLITAR - Aprilia Yugis Tri Waluyo; Yulianto D Saputro; Aprilia Yugis Tri Waluyo (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: Schools as educational institutions or academic institutions, are expected to be good and appropriate facilities for each student. Both in learning hours and outside of learning hours (extracurricular activities). The role of the Sports Teacher in improving extracurricular soccer activities at MI Negeri 7 Blitar Blitar Regency should be carried out properly. The school should have provided sufficient facilities and infrastructure for the implementation of extracurricular soccer activities for each student. MI Negeri 7 Blitar should be present as a facilitator and support in developing the sustainability of extracurricular soccer activities. This study aims to determine how much the role of sports teachers in improving extracurricular soccer activities at MI Negeri 7 Blitar. Research that uses descriptive methods through a naturalistic qualitative approach. This research data collection technique was carried out by means of observation, interviews, and documentation, and data analysis was carried out during the data collection process about the ongoing and when the data was all collected. So with regard to what is said above, the authors conclude that MI Negeri 7 Blitar as a school where learning and studying must also be a facilitator, provider and supporter of good extracurricular activities for each student. Starting from the procurement of soccer game equipment, such as enough balls, goals and adequate costumes according to the number of students participating in these extracurricular activities so that they can be motivated and have high enthusiasm.